The Association between Glucose Levels and Adverse Pregnancy Outcomes in Nondiabetic Twin Pregnancies - Kevin Cheung; Nathan S. Fox (Thieme Medical Publishers, Inc., 2020)
Objective The aim of this study is to determine if hyperglycemia in twin pregnancies without gestational diabetes mellitus (GDM) is associated with an increased risk of adverse pregnancy outcomes. Study Design Retrospective cohort study of twin pregnancies in a single Maternal-Fetal Medicine practice between 2005 and 2019 who underwent two-step GDM screening at 24 to 28 weeks. We excluded women with pregestational or gestational diabetes. We examined the association between maternal glycemia and adverse pregnancy outcomes. Glycemia was defined as the 1-hour GCT in all women, and each of the four values of the 3-hour OGTT in women who failed the GCT (≥130 mg/dL). Primary outcomes were preeclampsia, cesarean delivery, and neonatal hypoglycemia in either twin. Statistical tests used included Pearson's correlation, Student's t-test, Mann-Whitney U test, Chi-square test for trend, and logistic regression. Results A total of 847 women underwent a GCT and 246 women underwent an OGTT. Increasing maternal glucose levels had no positive association with adverse outcomes. Women with preeclampsia, cesarean delivery, and neonatal hypoglycemia did not have higher mean GCT or OGTT values than women without these outcomes. There was no increased risk of adverse outcomes with increasing quartiles of the GCT or OGTT values. Conclusion In women with twin pregnancies without GDM, elevated maternal glucose levels are not associated with preeclampsia, cesarean delivery, or neonatal hypoglycemia. The altered physiology of twin gestations may modify the effect of maternal hyperglycemia on perinatal outcomes as compared with singleton pregnancies. Current approaches to screening for and treating GDM during pregnancy might not adequately account for these unique considerations among twins.